Relación del modelo montessori con los resultados del aprendizaje en las áreas de matemática, lengua y literatura en el sub nivel básica elemental, en la unidad educativa Alicia Mackuard de Yerovi del cantón Salcedo, en el año lectivo 2013-2014 - Moncayo Moscoso, Marcela Cecilia (2015)
The education was based on an strict scheme in which one was treating the child as spectator and alone receiver of knowledge, and the teacher was not interested in the pupil was learning or not, simply the education was worked by the ancient saying of “the letter with castigate learns”; nevertheless Maria Montessori related that in the same way that a child learns the language and literacy skills in the same way learns to crawl and walk. This educational method was characterized by his emphasis on the activity directed by the child and clinical observation by the teacher. The basic intention of this method was to liberate the potential of every child so that it auto-develops in a structured atmosphere. The method was born of the idea of helping the child to obtain an integral development, to achieve a maximum grade in his intellectual, physical and spiritual capacities, working on scientific bases as regards the physical and psychic development of the child….